Area-based Medical Waste Management Issues in A Sustainable Environmental Perspective - Ni Made, Anggia Paramesthi Fajar; I Putu Andika Pratama; I Wayan Putu, Sucana Aryana; I Dewa Agung Ayu, Mas Puspitaningrat; Nathan Franklin (Indonesia Law Reform Journal, 2024)
Abstract Medical waste, which includes toxic and hazardous waste, is generated from activities that occur in health facilities and has the potential to transmit various disease-causing agents. Therefore, medical waste must be managed in accordance with the principles of area-based management. This research is a doctrinal legal research project that employs a combination of primary, secondary, and tertiary legal materials. The methodology for collecting legal materials involves a document study that incorporates both a statute and analytical conceptual approaches. The results and discussion demonstrate the unavailability of land for the management of medical waste, including toxic and hazardous materials. This situation compels healthcare facility management to form collaborative relationships with medical waste management companies specialising in the disposal of toxic and hazardous waste. Consequently, the management of medical waste at area-based healthcare facilities remains unfulfilled. Abstrak Limbah medis (limbah B3) pada dasarnya merupakan limbah hasil proses kegiatan yang terjadi di fasilitas kesehatan yang sifatnya sangat potensial dapat menularkan berbagai bibit penyakit. Sehingga limbah medis (limbah B3) perlu untuk dikelola dengan baik dengan prinsip pengelolaan berbasis wilayah. Penelitian ini merupakan penelitian hukum doktrinal dengan menggunakan bahan hukum primer, sekunder dan tersier. Teknik pengumpulan bahan hukum dilakukan dengan studi dokumen dengan pendekatan perundang-undangan dan pendekatan analisis konseptual. Hasil dan pembahasan yaitu adanya ketidaktersediaan lahan untuk membuat pengelolaan limbah medis (limbah B3) sehingga menjadikan fasilitas pelayanan kesehatan harus menjalin kerjasama dengan perusahaan pengelola limbah medis (limbah B3) dalam hal pengelolaannya. Sehingga berdasarkan hal tersebut masih belum dapat mewujudkan pengelolaan limbah medis (limbah B3) fasilitas pelayanan kesehatan berbasis wilayah.